Drought, Salinity, and Low Nitrogen Differentially Affect the Growth and Nitrogen Metabolism of Sophora japonica (L.) in a Semi-Hydroponic Phenotyping Platform - Tian, Jing; Pang, Yue; Zhao, Zhong (Frontiers in Plant Science, 2021)
Abiotic stresses such as salinity, drought and nutrient deficiency adversely affect nitrogen (N) uptake and assimilation in plants. However, the regulation of N metabolism and N pathway genes in Sophora japonica under abiotic stresses is unclear. S. japonica seedlings were subjected to drought (5% polyethylene glycol 6000), salinity (75 mM NaCl), or low N (0.01 mM NH4NO3) for 3 weeks in a semi-hydroponic phenotyping platform. Salinity and low N negatively affected plant growth, while drought promoted root growth and inhibited aboveground growth. The NH4+:NO3- ratio increased under all three treatments with the exception of a reduction in leaves under salinity. Drought significantly increased leaf NO2- concentrations. Nitrate reductase (NR) activity was unaltered or increased under stresses with the exception of a reduction in leaves under salinity. Drought enhanced ammonium assimilation with increased glutamate synthase (GOGAT) activity, although glutamine synthetase (GS) activity remained unchanged, whereas salinity and low N inhibited ammonium assimilation with decreased GS activity under salt stress and decreased GOGAT activity under low N treatment. Glutamate dehydrogenase (GDH) activity also changed dramatically under different stresses. Additionally, expression changes of genes involved in N reduction and assimilation were generally consistent with related enzyme activities. In roots, ammonium transporters, especially SjAMT1.1 and SjAMT2.1a, showed higher transcription under all three stresses; however, most nitrate transporters were upregulated under salinity but unchanged under drought. SjNRT2.4, SjNRT2.5 and SjNRT3.1 were highly induced by low N. These results indicate that N uptake and metabolism processes respond differently to drought, salinity and low N conditions in S. japonica seedlings, possibly playing key roles in plant resistance to environmental stress.